School-Based Mental Health Programs for Preadolescent Girls: Mitigating Social Contagion of Non-Suicidal Self-Injury - Tiedemann, Barbara L. (Canadian Journal of Counselling and Psychotherapy, 2022)
Current mental health disorder rates for preadolescent and adolescent girls demonstrate a disturbing trend, most notably a drastic increase in reports of non-suicidal self-injury (NSSI), especially in the age category of 10- to 14-year-olds. NSSI has become normalized in the adolescent population, and social contagion—the spreading of NSSI through peer and media influence—has become a significant concern. This article defines and discusses NSSI and social contagion and explores why preadolescent and adolescent girls may be particularly vulnerable to it. Further, current Canadian approaches to mental health promotion and primary prevention are reviewed, and an argument is made for the development and implementation of elementary school–based, gender-specific, comprehensive mental health programs. Incorporating interconnected evidence-based protective factors such as self-worth, self-compassion, emotion regulation, healthy relationships, communication, and family and school systems will provide young girls with valuable skills and knowledge to mitigate their engagement with NSSI and to resist social contagion.